Social Performance Management and Sustainability of Microfinance Institutions - Ghising, Tilak (International Research Journal of MMC, 2022)
Social performance management refers to the ability to achieve social goals by putting customers at the center of strategy and operations in microfinance institutions. The social performance of a microfinance institution means its effectiveness in achieving social goals and creating value for customers. This is just one aspect of social performance management. Social performance management examines the whole process through which an effect occurs. In the present study, social performance is considered as an assessment of social goals such as targeting the poor and marginalized, an adaptation of services that deliver economic benefits to customers, and the environment, and employees to improve social responsibility towards customers and the community. The overall performance of microfinance institutions contributes to the long-term sustainability of the organization. Sustainability of microfinance institutions means the long-term continuation of the microfinance program, which includes continuity of financial and non-financial services of microfinance institutions. The sustainability of microfinance institutions are measured by using a portfolio, performance, financial management, and profit-to-financial ratio. In the present study, the sustainability of microfinance considered as a long-term continuation of the program that benefits all stakeholders in the microfinance sector and society. Most microfinance institutions devote their efforts to achieving the social and financial goals of the organization. Social performance facilitates progress in achieving the social goals of microfinance institutions. As such, sustainability is a dynamic concept that aims to meet the expected cost of all programs and return on investment.